Port Strategy for Sustainable Development - Elvira Haezendonck (MDPI, 2021)
Today, most large port hubs include the circular economy transformation challenge, together with smart digitalization and Internet of Things (IoT), in their strategic priorities. However, many ports do not seem to have progressed beyond incremental, small-scale sustainable innovations or the support of rather fragmented sustainability initiatives. The challenges are complex, since ports do not only have to reconsider their own core activities but also their role in the supply chain of shippers, to lift themselves out of the linear lock-in. Opportunities are also created, and port authorities and businesses need to embrace circular learning and turn these projects into sustainable business models. This strategic change or refocus requires new insights into innovative governance and business frameworks, the link between strategy and commercially viable business models, systems innovation, intensified stakeholder collaboration and co-creation, altered traffic segments and hinterland focus, amongst others. These Special Issue articles address current CE transition concerns salient to port strategists and managers, such as first strategic changes towards circular ports, building awareness on the importance of sustainability data and available space, and how port authorities can develop circular business models
Keywords: 650; port masterplanning; corporate sustainability; traffic flow modeling; discrete-event simulation; sustainability reporting; inland ports; Triple Bottom Line; materiality analysis; stakeholder management; boundary setting; ecological perspective; port-city system; coordinated development; system dynamics; circular economy; circular supply chain management; secondary seaports; port authority; stevedores; port-related emission; cargo-handling equipment; emission inventory; external container trucks; air quality; maritime transport; emission from ships; sustainable port; energy sources; ship’ s crew and port pilots qualification; green shipping; environmentally friendly fuels; ports; port of Amsterdam; case study; circular economy ecosystem; port cities; public value; strategic management; incinerator capacity; green ports; scale development; stakeholders; corporate social responsibility; strategy; maturity; patterns; transition; process; circular initiative; case studies; Belgium